Everyman's database primer : featuring dBase III plus - Byers, Robert A. (Torrance, Calif. : Ashton-Tate Pub. Group, 1986)
This book provides a step-by-step guide to planning, creating, using ,modifying, and maintaining example database.
kjo 15/01/2019
Loans
Keywords: Database management; Dbase